2014
DOI: 10.1038/srep07484
|View full text |Cite
|
Sign up to set email alerts
|

Coral spawning in the Gulf of Oman and relationship to latitudinal variation in spawning season in the northwest Indian Ocean

Abstract: Despite a wealth of information on sexual reproduction in scleractinian corals, there are regional gaps in reproductive records. In the Gulf of the Oman in the Arabian Sea, reproductive timing was assessed in four common species of broadcast spawning corals using field surveys of gamete maturity and aquarium observations of spawning activity. The appearance of mature gametes within the same month for Acropora downingi, A. hemprichii, Cyphastrea microphthalma and Platygyra daedalea (≥ 75% of colonies, n = 848) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…24 release sites across eight source areas were modeled (Figure 8). Release was started at peak high tide at full moon on 27 April (8 a.m.) and continued for 8 days, finishing on 4 May 2010 (23.00), as was observed to be peak spawning period in the study area Howells et al, 2014). Release periods occurred twice a day following the 2 high tides, covering 16 tidal cycles, again comparable to field observations.…”
Section: Oceanographic Model Of Connectivitysupporting
confidence: 63%
“…24 release sites across eight source areas were modeled (Figure 8). Release was started at peak high tide at full moon on 27 April (8 a.m.) and continued for 8 days, finishing on 4 May 2010 (23.00), as was observed to be peak spawning period in the study area Howells et al, 2014). Release periods occurred twice a day following the 2 high tides, covering 16 tidal cycles, again comparable to field observations.…”
Section: Oceanographic Model Of Connectivitysupporting
confidence: 63%
“…; Howells et al. , ), while spawning occurs in the early spring on the Yemeni island of Socotra, in the Arabian Sea (Baird et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of coral settlement to tiles in the Sea of Oman was surprising. Reproductive studies occurring near these sites have shown that common coral species were spawning during this study in April 2013 (Howells et al, 2014), and fecundity was substantially higher than conspecifics in the southern Gulf (Howells et al, 2016). Additionally, juvenile surveys on these sites in 2012 showed that corals were recruiting to these reefs, although densities were half of that observed in the southern Gulf (Pratchett et al, 2017), suggesting that recruitment is impaired here.…”
Section: Coral Settlement Patternsmentioning
confidence: 91%
“…Due to its greater depth and exchange with the wider Indian Ocean, SSTs in the Gulf of Oman are less extreme (mean summer maxima <32 • C, range 10 • C annually) and salinity is comparable to oceanic conditions (37 PSU) (Foster et al, 2012;Howells et al, 2014). Its waters are also highly productive compared with the Gulf and Musandam as a result of monsoon-induced upwelling (Sheppard et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation